Meningkatkan Minat Belajar Bahasa Indonesia dengan Membandingkan Model Pembelajaran RADEC dan Model Pembelajaran Konvensional - Neneng Maryani; Karin Nurseptiani (MADROSATUNA : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2019)
This research is based on field findings, namely low interest in learning Indonesian, lack of teacher initiative to use varied learning models that cause students to become bored in following the learning process in Indonesian subjects. The purpose of this study is to find out the increased interest in learning Indonesian by comparing the RADEC (Read, Answer, Discuss, Explain, and Create) learning models and conventional learning. The research method used was Nonequivalent Control Group Design with a population of 173 students, and two sample classes namely class V as an experimental class totaling 28 students and class VI as a control class totaling 37 students. From the results by statistical data using SPSS version 24.0 for windows after the data are declared normally distributed and come from homogeneous samples through normality and homogeneity tests, it is known that the results of hypothesis testing using the Compare Means test with Independent Samples Test obtained sig = 0,000. Because the significance <0.05, it can be concluded that Ho is rejected, which means "There is a difference in the increase in interest in learning Indonesian by using the RADEC learning model compared to using the conventional model in SD Negeri Sukamaju, Pagerageung District, Tasikmalaya District". The score is in the interval 66.4 -70.1. Based on this, it can be concluded that the implementation of the RADEC learning model is quite successful in increasing interest in learning Indonesian compared to using conventional models. Suggestions that can be recommended based on the findings of this study include expected to be able to develop RADEC learning models that are collaborated with other learning techniques as an innovation to increase learning interest.